Multifunctional cleaning stick / Muhamad Shahaikal Md Yussof … [et al.] - Md Yussof, Muhamad Shahaikal; Jumadi, Nurfarhana Jazreen; Mohamad Razan, Sayidah Nafisah; Mohd Tarmidzi, Ain Maizatul; Araf, Nur Najah Amirah; Atan, Mohd Amirul (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The multifunctional cleaning stick revolutionizes cleaning by combining brush, wiper, sponge, and water spray functions in one device. It is in order to address challenges like the need for multiple tools and user fatigue. From there, with objectives to streamline the process, enhance efficiency, and improve user experience, this innovative tool offers versatile and ergonomic design, making it essential for households and commercial services. The multifunctional cleaning stick designed to simplify and enhance household cleaning processes. A significant impact lies in simplifying cleaning, reducing time and effort, adapting to various surfaces, and catering to a wide consumer base seeking efficient solutions. Additionally, its cost effectiveness is underscored by the long-term savings achieved through reduced reliance on disposable cleaning products and energy-efficient operation. Furthermore, user-friendly features such as lightweight construction, ergonomic design, and adjustable settings enhance convenience and comfort during use, ensuring effortless navigation and optimal cleaning results. Through the right efforts, the Multifunctional Cleaning Stick aims to become a must have item for homes, providing a practical solution to everyday cleaning routines.